Water Quality Measurements with TSS, TDS, Total Phosphate, Nitrate, Total Coliform Parameters in the Garang Water Shed - Syafrudin Syafrudin; Anik Sarminingsih; Henny Juliani; Mochamad Arief Budihardjo; Annisa Sila Puspita; Ikviy Ya’azzan Nabila (Universitas Diponegoro, 2023)
Massive industrial and urban development can cause changes in the quality of river water, one of which is the Garang Watershed, located in Central Java Province. This river is situated in Kendal Regency (upper and middle) and Semarang City (middle and lower). This research examined the Garang River's water quality conditions, divided into four sub-basins: Garang Hilir, Garang Hulu, Kreo and Kripik. The parameter assessed in this research is TSS, TDS, Total Phosphate, Nitrate, and Total Coliform Parameters with a total of ten sampling location points were determined based on several criteria using GPS and the SNI 6989.57:2008 sampling method. TSS and TDS concentrations in March-April were observed to be high, especially at sampling point 10. In contrast, total phosphate concentrations were elevated at sampling points 2, 3, and 9; Nitrate values were observed to be high at sampling point 3 in March and sampling point 5 in April; Total coliforms were high at sampling points 1, 3, and 4, all of these is possibly due to domestic waste and the use of fertilizer by agricultural activities. This sampling quality assessment shows a close relationship between human activities and agricultural activities in river water quality, especially in the Garang River.